Increased Peripheral Proinflammatory T Helper Subsets Contribute to Cardiovascular Complications in Diabetic Patients - Ru-xing Zhao; Wen-juan Li; Yi-ran Lu; Jun Qin; Chuan-long Wu; Meng Tian; Tian-yi He; Shou-nan Yi; Dong-qi Tang; Lei Sun; Li Chen (Mediators of Inflammation)
Background. Coronary atherosclerotic heart disease (CHD) is one of the major concerns in type 2 diabetes (T2D). The systemic chronic inflammation has been postulated to bridge the increased risk of cardiovascular disease and T2D. We formulated that increased peripheral proinflammatory T helper subsets contributed to the development of cardiovascular complications in diabetic patients. Methods. The frequencies of peripheral total CD4+ T helper cells, proinflammatory Th1, Th17, and Th22 subsets were determined by flow cytometry in diabetic patients with or without CHD (n=42 and 67, resp.). Results. Both peripheral frequencies and total numbers of Th1, Th17, and Th22 cells were further increased in diabetic patients with CHD. Logistic regression and categorical cross-table analysis further confirmed that increased proinflammatory Th subsets, especially Th22, were independent risk factors of cardiovascular complication in diabetes. Elevated Th subsets also correlated with increased CRP levels and the atherogenic index of plasma. Moreover, Th1 frequency and Th22 numbers demonstrated remarkable potential in predicting CHD in diabetes. Conclusions. Increased peripheral proinflammatory T helper subsets act in concert and contribute to the increased prevalence of diabetic cardiovasculopathy. The recently identified Th22 cells might play an independent role in CHD and represent a novel proxy for cardiovascular risks in diabetes.